Peradilan Pajak dan Kepastian Hukum di tengah Globalisasi Ekonomi - Tjip Ismail (Jurnal Hukum IUS QUIA IUSTUM, 2010)
This research discusses the problem of legal certainty in economic globalization and tax court as legal enforcement instrument and tax dispute settlement through tax court. This research uses qualitative research method which secondary data is legal source. Using this method, this research found: First, tax court might be an important instrument in the effort of creating legal certainty; Second, tax court is a court under Supreme Court which exercise court (kehakiman) power in the matter of taxation; Third, tax dispute is a dispute in the matter of taxation between subject of tax (wajib pajak) and government official which has authority in taxation.Key word : Tax court, legal certainty, economic globalization